Evaluación de extractos acuosos de aji y ajo sobre el crecimiento micelial de moniliophthora roreri a nivel in vitro - Medina Jaramillo, Yorman Vicente (Machala : Universidad Técnica de Machala, 2022)
Cocoa (Theobroma cacao), which in Greek is described as "food of the gods", is a plant that grows in tropical humid forests, for this reason its origin is restricted to certain areas of the planet. The African countries Ivory Coast and Ghana are the largest producers of regular cocoa in the world with around 65%, while Latin America concentrates 90% of fine aroma cocoa. It is estimated that, in Ecuador, of the 24 Provinces, 23 produce cocoa in different proportions and its production is a monoculture. The provinces with the highest concentration of this crop are: Los RÍos, Guayas, El Oro and Esmeraldas. The main diseases in cocoa cultivation are Moniliasis and Black Corn, its causal agents are Moniliophthora roreri and Phytophthora spp. To control Moniliasis, different alternatives are used to help contain the disease, such as the use of fungicides, endophytic fungi, organic fungicides and botanical extracts. Extracts of plant origin have the particularity of having secondary metabolites that make the plant form defense strategies against an attack by phytopathogens, among the metabolites found in plants are: phenols, flavonoids, terpene alkaloids, essential oils, lecithins and polypeptides. Based on the problem of not having adequate control for cocoa diseases, this research is based on the use of two plants: Garlic (Allium sativum) and Chili (Capsicum annuum), where we aim to determine what percentage of aqueous extract obtained better results, and from which it will be possible to obtain the secondary metabolites present to inhibit the mycelial growth of Moniliophthora roreri at the in vitro level. The treatments that were used in the investigation were the following: In the mean comparison test, in the growth averages T3 (aqueous extract of Garlic at 30%); T2 (aqueous extract of garlic at 20%); T9 (extract Aqueous extract of Garlic-Chili at 30%);T1(Aqueous extract of garlic at 10%);T8(Aqueous extract of Garlic-Chili at 20%);T4 (Aqueous extract of Chili at 10%);T5(Aqueous extract of Chili 20%); T7 (aqueous extract of Garlic-Chili); T6 (aqueous extract of Chili 30%); T10 (absolute control) these were the treatments applied with their corresponding doses. For the preparation of extracts we use three Erlenmeyer flasks where we place the fresh material of the different plants, in this case we use the chili and garlic bulbs, and in a mortar with pestle the macaques, the dosage that was used in each Erlenmeyer was: 60gr of garlic/300ml of distilled water; 60g of chili/300ml of distilled water and a combination of 30g of garlic – 30g of chili/300ml of distilled water, the final weight/volume ratio was 1:3.Under controlled laboratory conditions, the treatments that presented the greatest inhibitory effect were the T3 aqueous extract of garlic at 30% and T2 aqueous extract of garlic at 20%, both are statistically equal and different from the rest of the treatments, finally it is recommended to carry out studies focused on botanical extracts of plant origin with antifungal potential, as an alternative of control in the management of diseases caused by phytopathogenic fungi.
El cacao (Theobroma cacao), que en griego se describe como “comida de los dioses”, es una planta que crece en bosques húmedos tropicales, por tal motivo su origen se ve restringido a ciertas áreas del planeta. Los países africanos Costa de Marfil y Ghana son los mayores productores de cacao corriente del mundo con alrededor del 65%, mientras que en Latinoamérica concentra el 90% del cacao fino de aroma. Se estima que, en el Ecuador de las 24 Provincias, 23 producen cacao en diferentes proporciones y su producción es un monocultivo. Las provincias con la mayor concentración de este cultivo son: Los RÍos, Guayas, El Oro y Esmeraldas. Las principales enfermedades en el cultivo de cacao son Moniliasis y Mazorca negra sus agentes causales son Moniliophthora roreri y Phytophthora spp. Para el control de Moniliasis se emplean diferentes alternativas que ayuden a contener la enfermedad como el uso de fungicidas, hongos endófitos, fungicidas orgánicos y extractos botánicos. Los extractos de origen vegetal tienen la particularidad de poseer metabolitos secundarios que hace que la planta forme estrategias de defensa frente a un ataque de fitopatógenos, entre los metabolitos que se encuentran en las plantas son los: fenoles, flavonoides, alcaloides terpenos, aceites esenciales, lecitinas y polipéptidos. En base a la problemática de no haber un control adecuado para las enfermedades de cacao, la presente investigación se basa en el uso de dos plantas: Ajo (Allium sativum) y Ají (Capsicum annuum), en donde tenemos como objetivo determinar qué porcentaje de extracto acuoso obtuvo mejores resultados, y del cual se podrá obtener los metabolitos secundarios presentes para inhibir el crecimiento micelial de Moniliophthora roreri a nivel in vitro. Los tratamientos que se emplearon en la investigación fueron los siguientes: En la prueba de comparación de medias, en los promedios del crecimiento T3 (extracto acuoso de Ajo al 30%);T2 (extracto acuoso de ajo al 20% );T9 (extracto acuoso de Ajo-Ají al 30%);T1(extracto acuoso de ajo al 10%);T8(extracto acuoso de Ajo-Aji al 20%) ;T4 (extracto acuoso de Ají al 10%) ;T5(extracto acuoso de Ají al 20%);T7(extracto acuoso de Ajo-Ají);T6(extracto acuoso de Ají al 30%);T10(testigo absoluto) estos fueron los tratamientos aplicados con sus dosis correspondientes. Para la preparación de extractos utilizamos tres matraces Erlenmeyer donde colocamos el material fresco de las diferentes plantas, en este caso utilizamos los bulbos del ají y ajo, y en un mortero con pistilo los macacos la dosificación que se usó en cada Erlenmeyer fue: 60gr de ajo/300ml de agua destilada; 60gr de ají/300ml de agua destilada y una combinación de 30gr de ajo – 30 gr de ají / 300ml de agua destilada, la relación final peso/volumen fue 1:3.En condiciones controladas de laboratorio los tratamientos que presentaron mayor efecto inhibitorio son el T3 extracto acuoso de Ajo al 30% y T2 extracto acuoso de ajo al 20%, ambos son estadísticamente iguales y diferentes al resto de los tratamientos, finalmente se recomienda realizar estudios enfocados en extractos botánicos de origen vegetal con potencial antifúngico, como una alternativa de control en el manejo de enfermedades causadas por hongos fitopatógenos.
Keywords: HONGO; FITOPATÓGENOS; CACAO; EXTRACTOS